Pulmonary metastasectomy for colorectal cancer: How many nodules, how many times? - Kim, Hong Kwan (Baishideng Publishing Group Inc, 2014)
Colorectal cancer (CRC) is one of the most common cancers worldwide, with 5%-15% of CRC patients eventually developing lung metastasis (LM). Despite doubts about the role of locoregional therapy in the management of systemic disease, many surgeons have performed pulmonary metastasectomy (PM) for CRC in properly selected patients. However, the use of pulmonary metastasectomy remains controversial due to the lack of randomized controlled studies. This article reviews the results of surgical treatment of pulmonary metastases for CRC, focusing on (1) current treatment guidelines and surgical techniques of PM in patients with LM from CRC; (2) outcomes of PM and its prognostic factors; and (3) controversial issues in PM, focusing on repeated metastasectomy, bilateral multiple metastases, and combined liver and lung metastasectomy.